Dichotomy between Large Local and Small Ordered Magnetic Moments in Iron-Based Superconductors - Hansmann, Philipp; Arita, Ryotaro; Toschi, Alessandro; Sakai, S.; Sangiovanni, Giorgio; Held, Karsten (Physical Review Letters, 2010)
We study a four-band model for iron-based superconductors within the local density approximation combined with dynamical mean-field theory (LDA + DMFT). This successfully reproduces the results of models which take As p degrees of freedom explicitly into account and has several physical advantages over the standard five d-band model. Our findings reveal that the new superconductors are more strongly correlated than their single-particle properties suggest. Two-particle correlation functions unveil the dichotomy between local and ordered magnetic moments in these systems, calling for further experiments to better resolve the short time scale spin dynamics.
CRIS-Team WoS Importer:2020-02-19